The prognostic significance of smoking cessation after acute coronary syndromes: an observational, multicentre study from the Melbourne interventional group registry. Issue 10 (6th October 2017) - Yudi, Matias B; Farouque, Omar; Andrianopoulos, Nick; Ajani, Andrew E; Kalten, Katie; Brennan, Angela L; Lefkovits, Jeffrey; Hiew, Chin; Oqueli, Ernesto; Reid, Christopher M; Duffy, Stephen J; Clark, David J
Abstract : Objective: We aim to ascertain the prognostic significance of persistent smoking and smoking cessation after an acute coronary syndrome (ACS) in the era of percutaneous coronary intervention (PCI) and optimal secondary prevention pharmacotherapy. Methods: Consecutive patients from the Melbourne Interventional Group registry (2005–2013) who were alive at 30 days post-ACS presentation were included in our observational cohort study. Patients were divided into four categories based on their smoking status: non-smoker; ex-smoker (quit >1 month before ACS); recent quitter (smoker at presentation but quit by 30 days) and persistent smoker (smoker at presentation and at 30 days). The primary endpoint was survival ascertained through the Australian National Death Index linkage. A Cox-proportional hazards model was used to estimate the adjusted HR and 95% CI for survival. Results: Of the 9375 patients included, 2728 (29.1%) never smoked, 3712 (39.6%) were ex-smokers, 1612 (17.2%) were recent quitters and 1323 (14.1%) were persistent smokers. Cox-proportional hazard modelling revealed, compared with those who had never smoked, that persistent smoking (HR 1.78, 95% CI 1.36 to 2.32, p<0.001) was an independent predictor of increased hazard (mean follow-up 3.9±2.2 years) while being a recent quitter (HR 1.27, 95% CI 0.96 to 1.68, p=0.10) or an ex-smoker (HR 1.03, 95% CI 0.87 to 1.22, p=0.72) were not. Conclusions: In a contemporary cohort of patients with ACS, those who continued to smoke had an 80% risk of lower survival while those who quit had comparable survival to lifelong non-smokers. This underscores the importance of smoking cessation in secondary prevention despite the improvement in management of ACS with PCI and pharmacotherapy.